The impact of corporate social responsibility performance on earnings management: family versus non-family firms - Borralho, J; Gallardo-Vázquez, D.; Hernández-Linares, R.; Paiva, I. (43 EAA Virtual Annual Congress, 2021)
This study investigates the relationship between Corporate Social Responsibility (CSR) in environmental, social and corporate governance dimensions and earnings manipulation practices in family and non-family firms. We analysed 243 listed companies in France and Spain, two countries with code-law and concentrated ownership, from 2009 to 2018. The results show that CSR performance helps reduce levels of earnings management in family firms compared to non-family. The multidimensional nature of the concept of CSR may be differently reflected in the triple dimension of CSR performance in family firms, which reflects the quality of financial information. This evidence seems to be associated with the family's socio-emotional wealth, taking into consideration the company's concerns with image and reputation and the main stakeholders of CSR actions. Our study closes the gap in the literature on the relationship between CSR and the quality of financial information in family versus non-family firms.